2022
DOI: 10.1007/s11154-022-09748-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of testosterone in male sexual function

Abstract: Sexual function, and testosterone (T) levels, progressively decline in aging men. Associated morbidities and metabolic disorders can accelerate the phenomenon. The specific contribution of low T to sexual function impairment in aging men has still not been completely clarified. Similarly, the role of T replacement therapy (TRT), as well as the combination of TRT with phosphodiesterase type 5 inhibitors (PDE5i) for patients with erectile dysfunction (ED), is still conflicting. Here we aim to summarize and criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 106 publications
2
21
0
Order By: Relevance
“…Interestingly, both cross-sectional and longitudinal studies have shown that testosterone levels decline gradually as men age from their 30s to their 90s (48-50). Testosterone plays a role in every step of the male sexual response (51) with previous research showing that lower testosterone levels are associated with reduced sexual desire (52) and a higher risk of ED (52,53). In addition, testosterone replacement treatment can improve the latency times of men with acquired PE (PE appearing only after a man's rst sexual experience) (54).…”
Section: Age and Sexual Dysfunctionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, both cross-sectional and longitudinal studies have shown that testosterone levels decline gradually as men age from their 30s to their 90s (48-50). Testosterone plays a role in every step of the male sexual response (51) with previous research showing that lower testosterone levels are associated with reduced sexual desire (52) and a higher risk of ED (52,53). In addition, testosterone replacement treatment can improve the latency times of men with acquired PE (PE appearing only after a man's rst sexual experience) (54).…”
Section: Age and Sexual Dysfunctionmentioning
confidence: 99%
“…In addition, testosterone replacement treatment can improve the latency times of men with acquired PE (PE appearing only after a man's rst sexual experience) (54). However, a recent review has indicated that the effectiveness of testosterone replacement treatment in improving sexual function is modest and inconsistent, comparable to that of lifestyle interventions (53). In a similar vein, another contributing factor is cardiovascular disease contributing to ED with age (55).…”
Section: Age and Sexual Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…PM allows for identifying specific genetic markers [ 1 ], hormonal imbalances [ 2 3 ], and other physiological factors that contribute to sexual dysfunction. By analyzing an individual’s genetic and biochemical profiles, healthcare providers can better understand the root cause of sexual dysfunction; consequently, this can be used to design targeted treatment plans that address the unique factors contributing to a patient’s condition, resulting in more accurate diagnoses and improved outcomes.…”
Section: Improved Diagnostic Accuracymentioning
confidence: 99%
“…Interestingly, both cross-sectional and longitudinal studies have shown that testosterone levels decline gradually as men age from their 30s to their 90s [24][25][26]. Testosterone plays a role in every step of the male sexual response [27] with previous research showing that lower testosterone levels are associated with reduced sexual desire [28] and ED [28,29]. In addition, testosterone replacement treatment can improve the latency times of men with acquired PE (PE appearing only after a man's rst sexual experience) [30].…”
Section: Age and Sexual Dysfunctionmentioning
confidence: 99%